Using Automatic Vehicle Location System Data to Assess Impacts of Weather on Bus Journey Times for Different Bus Route Types - O'Mahony, Margaret (My University, 2021)
Weather has the largest collective effect on transport systems, affecting users of all modes at the same time over a wide area. The aim of the research is to use Automatic Vehicle Location System (AVLS) data to investigate the impact of adverse weather, using rainfall, temperature and wind speed as indicators, on bus journey time. It will also assess if the impacts are dissimilar across three bus route types: bus lanes on the entire route, bus lanes on part of the route and buses running in mixed traffic. Previous research tends to use bus ridership levels as the key variable of interest when exploring weather impacts whereas the approach taken here will examine bus journey times. Multiple linear regression and in-depth analyses are used to explore which weather variables have the greatest effects. Results indicate that more bus journey time variation can be explained by weather on weekdays than on weekends. Increases in rainfall, wind speed and temperature resulted in longer journey times, but the extent depends on the season and route type. The results will be useful to bus operators and local authorities in preparing mitigation strategies and for longer term planning, particularly in the context of climate change.
2021 IEEE International Intelligent Transportation Systems Conference (ITSC)
Keywords: Temperature distribution; Temperature dependence; Local government; Wind speed; Linear regression; Data models; Planning; Smart & Sustainable Planet; Environmental Impacts of Transport; Public Transport; extreme weather; Transport